2013
DOI: 10.1111/imj.12238
|View full text |Cite
|
Sign up to set email alerts
|

Causes of hospitalisation before and after the 2009 L'Aquila earthquake

Abstract: On 6 April 2009, an earthquake struck L'Aquila. The San Salvatore Hospital was evacuated, and a field hospital was built. The study aimed to assess the epidemiologic impact of the earthquake through the analysis of patient population admitted to the field hospital during a 2-month period following the disaster. We retrospectively evaluated causes of hospitalisation and demographic data of patients admitted to (i) the Division of Internal Medicine and (ii) the Division of Emergency Medicine of the field hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Eight studies related to food- and water-borne diseases and zoonoses and one to vaccine-preventable diseases; 25 two did not specify the pathogen or disease. 26 No deaths were reported in any of the outbreaks.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Eight studies related to food- and water-borne diseases and zoonoses and one to vaccine-preventable diseases; 25 two did not specify the pathogen or disease. 26 No deaths were reported in any of the outbreaks.…”
Section: Resultsmentioning
confidence: 94%
“…Another study looked at the incidence of infectious diseases in general following the L’Aquila earthquake. 26 This found that admission rates for infectious diseases rose from 7.41% before the earthquake to 27.18% in the 2 months following the earthquake. Rates of people diagnosed with an infectious disease but not requiring hospitalization also rose, from 12.04 to 27.29%.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations